2015
DOI: 10.3390/s151229791
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Hybrid Intelligent Indoor Location Method for Mobile Devices by Zones Using Wi-Fi Signals

Abstract: The increasing use of mobile devices in indoor spaces brings challenges to location methods. This work presents a hybrid intelligent method based on data mining and Type-2 fuzzy logic to locate mobile devices in an indoor space by zones using Wi-Fi signals from selected access points (APs). This approach takes advantage of wireless local area networks (WLANs) over other types of architectures and implements the complete method in a mobile application using the developed tools. Besides, the proposed approach is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…The influence radius, r a is sufficient for most studies with acceptable results ranged 0.1 to 0.7 [48,50]. A lower r a generates more clusters, these clusters be closer to each other and this would result in less errors.…”
Section: Fuzzy Clustering Subractivementioning
confidence: 99%
“…The influence radius, r a is sufficient for most studies with acceptable results ranged 0.1 to 0.7 [48,50]. A lower r a generates more clusters, these clusters be closer to each other and this would result in less errors.…”
Section: Fuzzy Clustering Subractivementioning
confidence: 99%
“…Surprisingly, none of these databases produced results by utilizing type-2 fuzzy in the problem of localization (of course using a specific set of keywords for both). Some studies in the field have been reported in [131][132][133][134]. Thus, the absence of such notification is justified from different viewpoints.…”
Section: Parametric Measures and Evaluationsmentioning
confidence: 99%
“…However, PDR results estimated from inertial measurement unit (IMU) data have errors that are accumulated over time. Thus, many methods have been proposed for correcting PDR positioning errors, such as combining various sensors and wireless devices for error correction [2,3] and conducting algorithmic advancements for obtaining heading direction and step length estimations [9][10][11][12][13][14][15][16]. This study optimised the PDR algorithm by using the difference magnetic fingerprint between real-time measurement and magnetic fingerprint map data to calculate the weight then put in a particle filter method (in this study call modified particle filter) to get the position of user.…”
Section: Introductionmentioning
confidence: 99%